Pergamon, Turkey. Monument Conservation and Capacity Building. The work of 2020 and 2021 - Mania, Ulrich; Tezer-Altay, Seçil (e-Forschungsberichte des DAI, 2022)
Highlight of 2020 was the finalisation of the conservation activities in the Red Hall, where several projects have been conducted since 2006. Furthermore in 2021 we finalized, the conservational efforts on the east retaining wall of the Gymnasium. In the same year, a new project has started focusing on retaining walls in danger of collapse at the theatre terrace. Besides this, urgent conservational works have been carried out in the Asklepieion, and at the Goths’ Wall since the grade of deterioration created imminent danger. All these works were accompanied by a capacity building project that has been running since 2019 with generous supports of the Gerda Henkel Foundation and the Culture Office of the German Ministry of Foreign Affairs, together with various local stakeholders.